(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this paper is to experimentally prove the ability of AC reactance of a transformer to automatically limit the short-circuit current and to adjust the output voltage. This transformer is able to change its reactance leakage resistance by moving the U-shaped iron mobile unit. It has three functions of voltage conversion, limiting the short-circuit current and voltage regulation. The CLT can limit the shortcircuit current in the circuit connected to the secondary winding at a very low level. It consists of an additional U-shaped core between the members. The design of the base region so that it bypasses the flow created by the short-circuit current and limits the secondary side current. In the event of a malfunction, an increase in the current in the secondary output circuit in the increase in the flow in the secondary winding, it will pass through an additional added base region. Thus, the current in the secondary winding does not exceed the rated current. The CLT provides a deeper current limit and may be more suitable for the distribution area. A large transformer can be used to meet the increased demand for a bus without a switch to increase the reliability of the distribution area.